A comparison of methods for extracting plasmids from a difficult to lyse bacterium: Lactobacillus casei. (January 2017) - Alimolaei, Mojtaba; Golchin, Mehdi
Abstract: There are few practical protocols to extract efficient plasmid DNA from the difficult-to-lyse bacterium, Lactobacillus casei . This is related to production of a large amount of exopolysaccharide coat and its special physiological characteristics. In this study, we optimized a protocol to extract efficient plasmid DNA from a recombinant L. casei strain. Different extraction methods were evaluated in three classes of conventional, kit-based, and combined protocols. The quantity and quality of the extracted plasmid DNA were determined by spectrophotometry, agarose gel electrophoresis, and PCR. Results revealed that the yield of the extracted plasmids differed for each protocol and conventional protocols showed higher plasmid yields. We suggested an effective, inexpensive protocol to extract plasmid DNA from the recombinant L. casei for downstream biological processes. Highlights: There are few protocols to extract plasmid DNA from difficult to lyse bacteria, Lactobacillus spp. We evaluated and compared eleven plasmid extraction protocols in three classes. We suggest an inexpensive protocol to extract effective plasmid DNA from L. casei.